1998
DOI: 10.1109/75.701379
|View full text |Cite
|
Sign up to set email alerts
|

Numerical dispersion and stability analysis of the FDTD technique in lossy dielectrics

Abstract: Two different extensions of the finite-difference timedomain (FDTD) method for the treatment of lossy dielectrics are considered: the time-average (TA) and the time-forward (TF) difference schemes. An analytical study of the stability properties and numerical dispersion of these schemes is presented. The stability analysis is based on the Von Neumann (Fourier series) method, while the numerical dispersion properties are established in terms of the numerical permittivity of discrete lossy dielectrics. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 3 publications
4
44
0
Order By: Relevance
“…µ nc nc (6) where ∆ξ and k ξ are spatial steps and wavenumbers in each x, y and z directions. nc and µ nc are known as the complex numerical permittivity and permeability which are unique to a particular FDTD scheme in doubly lossy media.…”
Section: Dispersion Analysis and Numerical Simulation For Doubly Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…µ nc nc (6) where ∆ξ and k ξ are spatial steps and wavenumbers in each x, y and z directions. nc and µ nc are known as the complex numerical permittivity and permeability which are unique to a particular FDTD scheme in doubly lossy media.…”
Section: Dispersion Analysis and Numerical Simulation For Doubly Lossmentioning
confidence: 99%
“…Stability analysis in [6][7][8] showed that for an electrically lossy medium, TA still preserves the stability criterion as the lossless FDTD scheme, i.e., the Courant-Friedrichs-Lewy (CFL) limit. On the other hand, TF and ETD have more relaxed and TB, more stringent stability criterion compared to the lossless CFL limit.…”
Section: Introductionmentioning
confidence: 99%
“…This is the dispersion relationship for lossy material which was previously considered in [22] and more recently studied in [23]. We define the complex permittivity to be…”
Section: Lossy Materialsmentioning
confidence: 99%
“…The dispersion relation of the FDTD (2,2) scheme in lossy dielectrics is found in Pereda et al (1998). To examine the accuracy of the scheme, we take the ratio of the numerical phase velocityc to the exact c:c…”
Section: Dispersion Analysis Of the Higher Order Schemesmentioning
confidence: 99%